Spontaneous abdominal hemorrhage due to warfarin treatment - Mustafa Volkan Demir; Tuba Öztürk Demir; Selcuk Yaylaci; Ahmet Bilal Genc (Wolters Kluwer Medknow Publications, 2016)
Warfarin is an anticoagulant used in the prevention of thromboembolism. Common clinical indications for warfarin use are atrial fibrillation, artificial heart valves, deep venous thrombosis. Common side effect of warfarin is hemorrhage. Intra-peritoneal hemorrhage is one of the complications, usually following trauma. We report spontaneous intra-abdominal hemorrhage secondary to warfarin therapy. A 79 year-old male patient was admitted to emergency clinic with the complaints of one day duration of abdominal pain. There was no history of trauma. He had been on warfarin for the prophylaxis of atrial fibrillation.The diagnosis of the spontaneous intra-abdominal bleeding secondary to warfarin was made and the patient was admitted internal medicine inpatient clinic.This case provides a learning lesson to the physicians to consider this rare but significant complication of warfarin in the differential diagnosis of all the cases of abdominal pain in patients who are on warfarin therapy.